MORPHOLOGICAL ANALYSIS ON MADURENESE AFFIXES IN THE SHORT STORY "JHA' ATOKARAN" - Lulua bin Muhammad Syafii; Muhammad Raka Yudi Athallah (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2023)
The aim of this research was to analyze the types of affixes and their functions in a short story written in the Madurese language titled "Jha' Atokaran". The method used in this study was qualitative descriptive analysis. The data source used was the text of the translated short story in Madurese. Data collection was done by reading and studying the short story and identifying the affixes used. Data analysis was conducted by classifying the types of affixes found in the story and understanding the function of each affix in shaping word structure and grammatical meaning. The results of this research was expected to provide a deeper understanding of the use of affixes in the Madurese language and their contribution to the structure and meaning of words in the short story "Jha' Atokaran".